Implicit motives and implicit emotions : testing the effect of motivated states on affect dimensions - Yeo, Zhi Zheng (2015)
The specificity hypothesis (McClelland, 1985) suggests that specific emotions (e.g., anger, happiness, and surprise) relate to specific motives (e.g., power, affiliation, and achievement). Zurbiggen and Sturman (2002) demonstrated weak linkages. Their weak evidence may be due to their use of measures of self-reported measures of affect. This is because conscious appraisals of emotions may cause reporting biases and distortion in the measurement. Subjects may also not be accurately aware of and hence fail to report their affective state. To eliminate these possible distortions, we test McClelland’s hypothesis via implicit measures of subjects’ affect.We aimed to test the following hypotheses: H1: There are significant higher mean levels of affect dimensions for the HS condition than the FF condition. H2: There are significant higher mean levels of affect dimensions at anticipatory stage than consummatory stage. H3: There are significant interaction effects of motive conditions and stage on affect dimensions. Mean levels of affect dimensions at anticipatory stage would be higher for the HS condition than the FF condition than that for the consummatory stage. [4th Award]